Analysis resistance and flow patterns of hull catamaran axe bow for tourism boat - Romadhoni Romadhoni; Budhi Santoso; Bobi Satria; Supriyadi Supriyadi (Jurnal Teknika, 2021)
The axe bow type catamaran is a ship used specifically for recreational purposes between Beting Island Aceh, which has two hulls (catamarans). This analysis aims to see a more reductive resistance value that can be used in the Beting Island Aceh  (Rupat) waters. To get the main size of the ship, namely the parent design approach method, which is to find data on the main ship and the same displacement to analyze the value of the ship's resistance. The main data of the ship, namely, LOA=12.20 m, B=4.089 m, H=1.48 m, T=0.62 m, ∆=7.243 tons. The resistance value of the axe bow type catamaran is smaller than the non-axe bow type catamaran, with a difference of 5.92%. Based on the results of running, the engine power of the axe bow type catamaran is 227 HP, while the non-axe bow type catamaran is 241 HP. Catamaran tipe axe bow adalah kapal yang digunakan khusus untuk rekreasi antar Pulau Beting Aceh yang memiliki dua lambung (catamaran). Analisis ini bertujuan untuk melihat nilai resistansi yang lebih reduktif yang dapat digunakan di perairan Pulau Aceh Beting (Rupat). Ukuran utama kapal diperoleh dengan menggunakan metode parent design approach, mencari data kapal induk dan displacement yang sama untuk menganalisa nilai hambatan kapal. Dan didapatkan data utama kapal yaitu LOA=12,20 m, B=4,089 m, H=1,48 m, T=0,62 m, =7.243 ton. Nilai hambatan kapal katamaran tipe axe bow lebih kecil dibandingkan dengan kapal katamaran tipe non axe bow dengan selisih sebesar 5,92%. Berdasarkan hasil running, tenaga mesin catamaran tipe axe bow adalah 227 HP, sedangkan catamaran tipe non axe bow adalah 241 HP.